Implementation of Generative Learning Models with Probing Question Methods in Static Fluid Learning - Hendini, Elvira; Akmam, Akmam; Gusnedi, Gusnedi; Sundari, Putri Dwi (Department of Physics Universitas Negeri Padang, 2023)
Learners who cannot connect the new knowledge received with previous knowledge will find it difficult to understand learning, causing low learning outcomes. The solution offered is to apply a generative learning model with the probing question method. The purpose of the study was to determine the effect of applying a generative learning model with probing question method on the learning outcomes of students in Static Fluid material class XI SMAN 14 Padang. The type of research is Quasi Experimental. The study population was all students of class XI MIPA. Sampling using purposive sampling technique. The research sample is XI MIPA 4 class as an experimental class and XI MIPA 5 class as a control class. A written page in the shape of an objective serves as the tool. The findings revealed a substantial contrast between classes using PBL learning models with probing question techniques and classes using generative learning models with these techniques in terms of the learning outcomes of the students. When compared to the control class, the experimental class's average learning outcomes were 81, while it was 78.4. At a significant threshold of alpha = 0.05, it was determined that tcount = 8.704 and ttable = 1.995 based on the equality test of the two averages. If ttable< tcount, then H0 must be disregarded. The significance of tcount lies in the rejection of H0 and acceptance of H1, which demonstrate that the generative learning model with the probing question method has a beneficial impact on learning outcomes.